2020
DOI: 10.47552/ijam.v11i2.1403
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Management of Rett Syndrome by Wholistic approach

Abstract: Background: Rett syndrome-RS comes under Autism spectrum disorder-ASD which is a neurodevelopmental syndrome. It is diagnosed by the main differentiating features of lack of interpersonal and communication skills, poor eye contact, delayed speech with pervasive abnormal body movements. Aim and Objectives: This case report is aimed at dissemination of comprehensive role of Ayurveda in management of ASD, Rett syndrome. Material and Methods: RS is the severe form of ASD. This case study of 2.3 year’s girl present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study also reported that Suvarnaprashan along with other Ayurveda medicines are most effective in treating all types of learning and mental disabilities in children [8] . The effectiveness of Suvarnaprashan in various developmental disabilities in children was reported earlier studies [5][6][7][8] . However, its effectiveness for children with pure delayed speech and language disorder without any associated developmental difficulties was not studied previously.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Another study also reported that Suvarnaprashan along with other Ayurveda medicines are most effective in treating all types of learning and mental disabilities in children [8] . The effectiveness of Suvarnaprashan in various developmental disabilities in children was reported earlier studies [5][6][7][8] . However, its effectiveness for children with pure delayed speech and language disorder without any associated developmental difficulties was not studied previously.…”
Section: Introductionmentioning
confidence: 63%
“…[3] Previous studies also reported that regular doses of Suvarnaprashan improves child's intellect, grasping power, sharpness, analysis power, memory recalling in an unique manner and nurture early developmental milestones [4] . It was also reported that it reduces aggressiveness, irritability, anxiety and attention seeking behaviour hence it is also provide benefit for children with various developmental disability such as learning disability, autism, attention deficits with or without hyperactivity disorder, cerebral palsy and many other disorders related to CNS [3][4][5] . Delayed in acquiring language is most common symptoms of childhood developmental disability affecting around 5 to 10% of all children [6] and majority of not have any other significant developmental difficulties [7] In previous case study, Suvarnaprashan interventions were implemented along with holistic approach in autism spectrum disorder and promising results in all developmental milestones was reported [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation